Environmental consequences of uranium atmospheric releases from fuel cycle facility: II. The atmospheric deposition of uranium and thorium on plants. (March 2015) - Pourcelot, L.; Masson, O.; Renaud, P.; Cagnat, X.; Boulet, B.; Cariou, N.; De Vismes-Ott, A.
Abstract: Uranium and thorium isotopes were measured in cypress leaves, wheat grains and lettuce taken in the surroundings of the uranium conversion facility of Malvési (South of France). The comparison of activity levels and activity ratios (namely 238 U/ 232 Th and 230 Th/ 232 Th) in plants with those in aerosols taken at this site and plants taken far from it shows that aerosols emitted by the nuclear site (uranium releases in the atmosphere by stacks and 230 Th-rich particles emitted from artificial ponds collecting radioactive waste mud) accounts for the high activities recorded in the plant samples close to the site. The atmospheric deposition process onto the plants appears to be the dominant process in plant contamination. Dry deposition velocities of airborne uranium and thorium were measured as 4.6 × 10 −3 and 5.0 × 10 −3 m s −1, respectively. Highlights: Uranium and thorium were measured in plants near the uranium conversion facility. Activity ratios show that emissions account for the high activities recorded in the plants. The atmospheric deposition process appears to dominate in plant contamination. Dry deposition velocities of airborne uranium and thorium were determined.